Mobile and electronic applications of resuscitation documentation: A systematic literature review - Putu Ita Purwanti Diansari; Sidik Awaludin (Politeknik Negeri Subang, 2026)
Background: Accurate and timely documentation during in-hospital cardiac arrest (Code Blue) is essential for patient safety and quality improvement; however, paper-based documentation is frequently incomplete and delayed. Purpose: This study aimed to evaluate the effectiveness of digital and electronic resuscitation documentation tools in improving documentation completeness, timing accuracy, and adherence to resuscitation algorithms compared with paper-based methods. Method: A systematic literature review was conducted using databases including Scopus, PubMed, ProQuest, and ScienceDirect, covering studies published from 2016 to 2025. Study quality was assessed using the JBI Critical Appraisal Tools. A total of ten studies were included, comprising six randomized controlled trials, three quasi-experimental studies, and one cross-sectional study. Two studies additionally incorporated qualitative components as part of a mixed-methods design. Results: Digital systems such as CPReCoder and NeRD demonstrated higher documentation completeness and more accurate time stamping. Cognitive aid–based applications, including Guiding Pad, Code Blue Leader, and PediAppRREST, improved guideline adherence, reduced critical errors, and lowered cognitive workload among resuscitation team leaders. However, most evidence was derived from simulation-based studies. Conclusion: Digital resuscitation documentation systems show strong potential to enhance documentation quality and resuscitation performance. Effective implementation requires user-centered design, adequate training, integration with electronic health records, and further validation through real-world clinical settings to support nursing practice and patient safety.